Hubungan Antara Kemampuan Berpikir Kritis Matematis Dan Kemandirian Belajar Siswa SMA Cimahi - A'ine Nurfalah; Dessy Prihatini; Wahyu Hidayat; Euis Eti Rohaeti (Journal on Education, 2019)
This study aims to determine about "The relationship mathematical critical thinking skills and Self-Regulated Learning of Cimahi High School students". This research is an experimental study with one sample class, namely the experimental class. The population in this study were all high school students in Cimahi City, while the selected sample was class X as the experimental class. The instruments in this study include, instrument tests consisting of 5 items of mathematical critical thinking and 30 items of Self-Regulated Learning questionnaire. The research method used is a method of correlation with quantitative approaches. Data analysis techniques used normality test and correlation test to find out the relationship between critical thinking and student Self-Regulated Learning. The results of this study indicate that there is an increase in critical thinking skills mathematically by using the Self-Regulated Learning of Cimahi High School students. The results are seen that the value of Pearson correlation is 0.802 indicating the strength of the relationship between students' critical thinking mathematically and student Self-Regulated Learning, because of the Sig. for 0,000 less than 0.05, it can be concluded that the strength of the relationship between students' critical thinking mathematically and student Self-Regulated Learning is significant.